English Corner at PGRI 7 Vacational High School English Room for Students at SMK PGRI 7 - Sulistiyani Sulistiyani; Dewi Rosaria Indah; Tri AE; Sri Nurhidayah; Apsari Fajar Prihantini; Indahria TH (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
The Community Partnership Program (PKM) aims to increase the creativity of English teachers and overcome several problems such as lack of understanding of learning methods, administrative limitations, learning tools and infrastructure. The solutions offered include providing training to vocational school teachers, providing learning tools according to the curriculum, making teaching aids, building adequate facilities and infrastructure, and holding training to design innovative learning tools. Solution methods for partners involve Information Technology (IT) training, using media and conversation modules as teaching materials, as well as providing English conversation modules for vocational students. Apart from that, internships are recommended for STKIP Bina Insan Mandiri students. The target of this PKM activity is to help English teachers improve the learning process and learning outcomes, as well as increase vocational school students' ability to communicate actively using English through conversation.